PENERAPAN MODELING INSTRUCTION DAN SIMULASI PHET DALAM MENINGKATKAN KEMAMPUAN MENGANALISIS - Hati, Hilmi Setia; Sapiruddin, Sapiruddin (Kappa Journal, 2020)
This study aims to determine the increase in students' ability to analyze by applying modeling instruction and simulation media PhET. The research method used is a quasi experimental method with one group pretest posttest design. In this study, samples were taken as many as 33 people. The instrument used in the study was a multiple choice test. This test consists of 5 questions in the analyze category. Data analysis in this study used the Gain Normality Test. From the calculation results obtained an average value of N-gain of 0.7, it can be concluded that the application of modeling instruction and simulation media PhET can improve the ability to analyze students.